New Markers for Management of Mesothelioma - Nash, Alistair; Firth née Phan, Tina; Creaney, Jenette (Seminars in Respiratory and Critical Care Medicine, 2023)
In this review, we provide an update on the status of cancer biomarkers for the clinical management of pleural mesothelioma, an aggressive cancer associated with asbestos exposure. Mesothelioma can be difficult to diagnose, and response to treatment is transient, even with recently adopted immune checkpoint inhibitor (ICI) combinations. Identification of mesothelioma-specific biomarkers could facilitate early diagnosis and tailor treatment strategies. Mesothelioma is characterized by frequent loss or alteration of the tumor suppressor genes cyclin-dependent kinase inhibitor 2A (CDKN2A) and BRCA1-associated protein-1 (BAP1). Accumulating data show these genes and/or their related protein products will be valuable tissue-based biomarkers for mesothelioma. Loss of BAP1, CDKN2A, p16, or methylthioadenosine phosphorylase provide pathologists with a reliable means of differentiating between mesothelioma and reactive mesothelial cell proliferations. This can aid diagnosis in difficult cases and is requisite for the identification of the new pathological entity malignant mesothelioma in situ. However, limited progress in identifying clinically useful soluble biomarkers in this cancer type has been made, with mesothelin remaining the benchmark. To date, results from studies to identify predictive biomarkers for ICI response have been disappointing. A recent retrospective study demonstrated BAP1 loss was predictive of improved survival following combination pemetrexed- and platinum-based chemotherapy. Validation of this result could have important clinical implications. Clinical trials aimed at targeting therapy based on biomarker expression are generally in the early phase setting, with overall results being moderate. The identification of biomarkers for mesothelioma remains a key research question due to their potential to improve patient outcomes in this deadly cancer.
Keywords: mesothelioma; biomarkers; BAP1; CDKN2A; mesothelin